Pengaruh terapi murottal al’quran terhadap tingkat kecemasan pada ibu hamil trimester III - Maulidar Maulidar; Adri Idiana; Evi Zahara; Sulastri Sulastri; Cut Yuniwati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Anxiety in pregnant women in the third trimester reaches 28.7% in Indonesia, negatively impacting the health of the mother and fetus. The limitations of pharmacological interventions include the possibility of side effects on the fetus, so non-pharmacological therapy, such as murottal, Al-Qur’an, becomes an alternative. Murottal treatment has been proven to be effective in reducing anxiety through alpha wave stimulation that calms the autonomic nervous system. Purpose: to determine the effect of murottal Al-Qur’an therapy on anxiety levels in pregnant women in the third trimester. Method: This study used a quantitative design with a quasi-experimental method (quasi-experiment), pre-test, post-test, and control group. A sample of 46 pregnant women in the third trimester at the Sukamakmur Health Center was selected using purposive sampling and divided into two groups: an intervention group (listening to murottal Al-Qur’an Surah Maryam for 25-30 minutes every day for 2 weeks) and a control group (no intervention). Anxiety levels were measured using the HRS-A questionnaire before and after the intervention. Data analysis employed the Wilcoxon test for within-group differences and the Mann-Whitney test for between-group differences. Results: The results of the bivariate analysis revealed a significant difference in the average anxiety score between the intervention group before and after the intervention (p-value = 0.000), but there was no difference in the control group (p-value = 0.062). There was a difference in the average anxiety score between the intervention group and the control group in pregnant women (p-value = 0.013). Conclusion: Al-Quran murottal therapy is effective in reducing the level of anxiety in pregnant women in the third trimester in the Sukamakmur Health Center work area.It is recommended for health workers to integrate murottal therapy into antenatal services, as well as educate pregnant women about the benefits of murottal treatment as an independent effort to reduce anxiety during pregnancy.